Food allergies in adults - Prasertcharoensuk, Amornrat (Journal of Medicine and Health Sciences, 2021)
Food allergies are an abnormal immune response to food and important conditions, especially among food allergies in adults. Disease progression and food allergens for adults are different than those of children. Food intolerance is often mistaken for a food allergy. Specialists are required to make the diagnosis. This article reviews food allergies related to the immune system, both IgE-mediated and cell mediated response. Some types of food allergies in adults, such as food associated exercise-induced anaphylaxis or oral allergy syndrome, would not be found in children. This review provides relevant symptoms and the diagnosis of food allergies in adults that may be helpful for further education and practice.